Analysis of climate extremes over the Arabian Peninsula using downscaled RCM data - Almazroui, Mansour (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2023)
Climate change is likely to severely affect the economies of countries in the Arabian Peninsula and make their populations vulnerable to weather extremes. This study aimed to investigate the changes in future temperature and precipitation extreme indices over the Arabian Peninsula using regional climate model simulations for the future time slices mid-century (2036-2065) and end-century (2071-2100) with respect to the reference period (1976-2005). For this purpose, three Global Climate Models (GCMs) simulations from the WCRP Coupled Model Intercomparison Project phase 5 (CMIP5) are downscaled over the Arabian Peninsula using the International Centre for Theoretical Physics (ICTP) Regional Climate Model (RegCM4). The results show that the warm days/nights (TX90p/TN90p) will increase more than 50% over most parts of the Arabian Peninsula. Warm spell duration index (WSDI) will increase over the Arabian Peninsula while the cold spell duration index (CSDI) will decrease in the mid-century under the high-emission scenario. The number of cold days/nights (TX10p/TN10p) will decrease over most parts of the Arabian Peninsula in the middle of the 21st century. The number of very wet days will increase over the whole Arabian Peninsula under both scenarios (RCP4.5 and RCP8.5). Towards the end-century, it will decrease in the central and southern regions under both scenarios. Heavy rainfall days will increase over the Arabian Peninsula in the mid-century. By the end-century, the number of heavy-precipitation days will mix of decrease and increase depending on region to region and model to model. Overall, the extreme precipitation is projected to increase rather than decrease at the end-century under both scenarios. The number of consecutive dry days (CDD) will increase over a large area of central and western Arabian Peninsula under the moderate scenario in the mid-century while it will decrease under the high-emission scenario. The present findings indicate that a careful interpretation of climate projections is needed for policy purposes as well as for climate change impact and adaptation related studies.